2010
DOI: 10.1007/s10096-010-0942-y
|View full text |Cite
|
Sign up to set email alerts
|

Superinfection during treatment of nosocomial infections with tigecycline

Abstract: We performed a retrospective and observational study of 51 patients treated with tigecycline, as the treatment for nosocomial infections due to multidrugresistant microorganisms, to evaluate the superinfection rate and their etiologies. Superinfections were diagnosed in 12 (23.5%) patients (seven due to Pseudomonas aeruginosa, 13.7%) and one patient had P. aeruginosa colonization. Five patients with superinfection died (41.6%), three due to superinfections and two to underlying diseases. The superinfection rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
0
16
1
Order By: Relevance
“…The problem arising with widespread use of tigecycline is the emergence of increased rates of PA infection, or infections by other microorganisms with reduced susceptibility to this antibiotic. A recent study indicates that the risk of superinfection rates, particularly on account of PA, increased during tigecycline therapy [9]. The authors reported PA superinfection in 13.7% of 51 patients, a higher rate than previously reported [10,11].…”
Section: Discussioncontrasting
confidence: 48%
“…The problem arising with widespread use of tigecycline is the emergence of increased rates of PA infection, or infections by other microorganisms with reduced susceptibility to this antibiotic. A recent study indicates that the risk of superinfection rates, particularly on account of PA, increased during tigecycline therapy [9]. The authors reported PA superinfection in 13.7% of 51 patients, a higher rate than previously reported [10,11].…”
Section: Discussioncontrasting
confidence: 48%
“…In a recent retrospective study of 51 patients treated with tigecycline for nosocomial infections due to MDR microorganisms, superinfection was diagnosed in 23.5% of patients. P. aeruginosa was the most frequent pathogen as in our study [17]. In another retrospective study, superinfection was detected in 7 of 21 patients and the isolated pathogens were E. aerogenes, K. pneumoniae, and P. aeruginosa [15].…”
Section: Discussionmentioning
confidence: 65%
“…However, there was no increase in the isolation rate of P aeruginosa in our study, although it ranked the first among the most frequent pathogens in hospital-acquired infections and was responsible for 12.4% (148/1186) of the cases reported in the study hospital in 2009 (Data from Infection Control Committee). Unlike in a previous study, 17 in this study, we included not only cases of nosocomial infection. Besides, many cases in the study received antipseudomonal antibiotics before tigecycline treatment.…”
Section: Discussionmentioning
confidence: 82%
“…The superinfection rate with tigecycline usage ranged from 2.4% to 23.5% across different studies. 17,18 GarciaCabrera et al 17 had reported that P. aeruginosa caused 58.5% superinfections at an average of 8 days of tigecycline treatment for nosocomial infections. Five cases (7.5%) in the study had bacterial isolation other than those causing their primary infections.…”
Section: Discussionmentioning
confidence: 98%